El juicio crítico sobre la literatura latina antigua satírica en la historia literaria del XVIII - Sánchez Manzano, María Asunción (2020)
La crítica de la literatura latina antigua comenzó a escribirse a partir de los comentarios de época imperial romana. Esta crítica antigua sirvió de pauta también para realizar una síntesis de la evolución de la literatura latina a la luz de la razón ilustrada. Sin embargo, la diversificación de los poemas humorísticos en lengua vernácula había desenfocado los rasgos auténticos de la sátira antigua, uno de los géneros literarios más característicos de Roma desde Lucilio.
The critical judgement on ancient Roman literature started in early times of Empire. Those comments were collected by some scholars during the Enlightenment. It was then, when they summarized the deeds of Roman authors and their contribution to the European literature as well, under the light of reason. Labouring this synthesis, they did not confirm the ancient theory about the early beginnings of Roman satire, as a representative Latin genre since Lucilius. The humorous poems in vernacular were so diverse, that it was difficult to know the very features of this ancient Roman genre.
Keywords: Sátira latina -- Historia y crítica -- 1701-1800; Crítica literaria